Talon Cusp: A Prevalence Study of Its Types in Permanent Dentition and Report of a Rare Case of Its Association with Fusion in Mandibular Incisor. (21st January 2014) - Sharma, Gaurav; Nagpal, Archna
Abstract : Purpose. The data on various types of talon cusp, a rare developmental anomaly that occurs predominantly on palatal surfaces of maxillary incisors with varied prevalence in different populations, is scarce. Thus, the purpose of study was to evaluate prevalence of various types of talon cusp and its association with sex predilection, site, and other dental anomalies and complications. Subjects and Methods. A cross-sectional prevalence study for various types of talon cusp was conducted in 5200 patients selected randomly. Hattab's classification criterion was used for diagnosis of types of talon cusp. The clinical diagnosis was confirmed with radiograph. Results. The prevalence of talon cusp was found to be 0.02% (1 in 430 cases). 12 cases of talon cusp in 10 patients (60% males) were documented (2 bilateral cases and 8 unilateral). Type I talon cusp and type II talon cusp were present in five cases each (40.1%) and type III talon cusp was observed in two (16.2%) cases. Conclusion. Type I talon cusp and type II talon cusp were the most common types and permanent maxillary central incisor was the most commonly involved tooth (50%). An extremely rare case of talon cusp on a fused permanent mandibular incisor is also reported.